Oligotrophic Growth of Nitrate-Dependent Fe2+-Oxidising Microorganisms Under Simulated Early Martian Conditions - Price, Alex; Macey, Michael C.; Pearson, Victoria K.; Schwenzer, Susanne P.; Ramkissoon, Nisha K.; Olsson-Francis, Karen (Frontiers in Microbiology, 2022)
Nitrate-dependent Fe2+ oxidation (NDFO) is a microbially-mediated process observed in many anaerobic, low-nutrient (oligotrophic) neutral-alkaline environments on Earth, which describes oxidation of Fe2+ to Fe3+ in tandem with microbial nitrate reduction. Evidence suggest that similar environments existed on Mars during the Noachian epoch (4.1-3.7 Ga) and in periodic, localised environments more recently, indicating that NDFO metabolism could have played a role in a potential early martian biosphere. In this paper, three NDFO microorganisms, Acidovorax sp. strain BoFeN1, Pseudogulbenkiania sp. strain 2002 and Paracoccus sp. strain KS1, were assessed for their ability to grow oligotrophically in simulated martian brines and in a minimal medium with olivine as a solid Fe2+ source. These simulant-derived media were developed from modelled fluids based on the geochemistry of Mars sample locations at Rocknest (contemporary Mars soil), Paso Robles (sulfur-rich soil), Haematite Slope (haematite-rich soil) and a Shergottite meteorite (common basalt). The Shergottite medium was able to support growth of all three organisms, whilst the contemporary Mars medium supported growth of Acidovorax sp. strain BoFeN1 and Pseudogulbenkiania sp. strain 2002; however, growth was not accompanied by significant Fe2+ oxidation. Each of the strains were also able to grow in oligotrophic minimal media with olivine as the sole Fe2+ source. Biomineralised cells of Pseudogulbenkiania sp. strain 2002 were identified on the surface of the olivine, representing a potential biosignature for NDFO microorganisms in martian samples. The results suggest that NDFO microorganisms could have thrived in early martian groundwaters under oligotrophic conditions, depending on the local lithology. This can guide missions in identifying palaeoenvironments of interest for biosignature detection. Indeed, biomineralised cells identified on the olivine surface provide a previously unexplored mechanism for the preservation of morphological biosignatures in the martian geological record.